RE_Configured Reality - Zinoski, Mihajlo (University of Belgrade – Faculty of Architecture Society for Aesthetics of Architecture and Visual Arts Serbia (DEAVUS), 2015)
One of the major issues of the capital of Macedonia, Skopje, nowadays has been the definition of the public space phenomenon and the recognition of the autopoietic discourse of new public buildings. We are facing the construction of “neoclassical” buildings as well as façade reconstructions of the existing buildings originating from the socialist era in Macedonia. An assumption can be made that this change of the objective social reality derives from decade long political, territorial and cultural influence of neighbouring countries that has caused a disappearance of the national identity in the public architecture in the city of Skopje. This type of influence has contributed to the dominant presence of modern architecture in the city of Skopje. The historical architectural elements that have been implemented in the construction of the new public buildings represent timeless fragments of past styles that do not exist any longer. The elements that have been taken and adapted lead to the possibility of their explicit relation to the language of the constructed buildings that has been reinterpreted in the new objective reality. Analyzing the phenomenology of the new architectural form/space, we make an effort to establish a correlation between the signification and the meaning from recipient’s point of view, who observes the world as a symbol where the distinction between reality and truth is by itself unreal. A conclusion will be proposed that the neoclassical architecture in the city of Skopje is a media projection, an attempt to re-establish the long lost identity where the building has no need of ideological content of the national identification. It has to represent a piece of work with incorporated historical meaning. The historical evolution of the terms mimesis and simulacrum will display that architecture in plural societies today is a medium of mass culture and populism. The consequent analysis is expected to show that in the communication process the architectural work as a medium represents a symbol in which the connoted has an a priori meaning i.e. the architectural work hasn’t got a phenomenon interaction with the recipient, it only means information instead. The final considerations are expected to realize that the phenomenon transformation of the new architectural space/building of “Skopje 2014“ Project does not have a dialectic relation with actual reality. Instead of representing the reality architectural work is a simulation rooted in history. It is immanent to the reproduction layers where one cannot find its beginning, not until the moment when the difference between the truth and the lie disappears.